Exploring the Next Frontier for Tobacco Control: Nondaily Smoking among New York City Adults. (20th May 2012) - Sacks, Rachel; Coady, Micaela H.; Mbamalu, Ijeoma G.; Johns, Michael; Kansagra, Susan M.
Abstract : Objective . Among current smokers, the proportion of Nondaily smokers is increasing. A better understanding of the characteristics and smoking behaviors of Nondaily smokers is needed. Methods . We analyzed data from the New York City (NYC) Community Health Survey to explore Nondaily smoking among NYC adults. Univariate analyses assessed changes in Nondaily smoking over time (2002–2010) and identified unique characteristics of Nondaily smokers; multivariable logistic regression analysis identified correlates of Nondaily smoking in 2010. Results . The proportion of smokers who engage in Nondaily smoking significantly increased between 2002 and 2010, from 31% to 36% (P = 0.05 ). A larger proportion of Nondaily smokers in 2010 were low income and made tax-avoidant cigarette purchases compared to 2002. Smoking behaviors significantly associated with Nondaily smoking in 2010 included smoking more than one hour after waking (AOR = 8.8, 95% CI (5.38–14.27)); buying "loosies" (AOR = 3.5, 95% CI (1.72–7.08)); attempting to quit (AOR = 2.3, 95% CI (1.36–3.96)). Conclusion . Nondaily smokers have changed over time and have characteristics distinct from daily smokers. Tobacco control efforts should be targeted towards "ready to quit" Nondaily smokers.